Los libros de texto de matemáticas en la enseñanza secundaria de Costa Rica (ING) - Murillo, Mario (2003)
The student textbook is an important consideration in understanding the educational landscape, both in its historical evolution and in its present state, especially in mathematics. This article describes some textbooks published in Costa Rica from the times of Bachelor Osejo to recent years. Some didactical issues are discussed, especially concerning textbooks published after 1964